The Utilization of the GeoGebra Application in Improving Junior High School Students’ Understanding of Geometry Concepts - Lubis, Tsuwaibatul Aslamiyah (PT. Anagata Sembagi Education, 2025)
This study aims to investigate the effectiveness of the GeoGebra application in enhancing students’ conceptual understanding of geometry at the junior high school level. Using a quasi-experimental design with a nonequivalent control group, the research involved two classes: one taught using GeoGebra (experimental group) and the other taught using conventional methods (control group). Both groups were given pre-tests and post-tests to assess their understanding of geometric concepts such as angles, shapes, and transformations. The results showed a significant increase in the post-test scores of the experimental group compared to the control group. Gain score analysis also revealed that students in the GeoGebra-assisted class achieved higher learning improvements. The use of GeoGebra helped visualize abstract geometric concepts in a dynamic and interactive way, which enhanced students’ engagement, comprehension, and motivation. The findings support the integration of interactive digital tools in mathematics instruction to foster meaningful learning and improve student outcomes, especially in abstract and visual topics like geometry.